The Risk Analysis on the Siam Banjar Orange Supply Chain Distribution Channel in Barito Kuala Regency - Karimal Arum Shafriani; Hartoni Hartoni (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2021)
Siam orange is a horticultural commodity that is very suitable and suitable for soil conditions for cultivation in tidal swamps. Wrong one area for the development of the Siam Banjar orange in South Kalimantan is located in the Barito Regency Kuala. As one of the agricultural commodities, Siam Banjar orange has high enough risk, so it needs good management in terms of this is called risk management. This study aims to identify Siam Banjar orange distribution channels, identify and analyze risks that occur in the supply chain distribution channel of Siam Banjar oranges, as well measure the risk on each member of the supply chain and search for those members that have the greatest risk. The data analysis method used is descriptive analysis, methods Analytical Network Process (ANP) and Weighted Failure Mode and Effects Analysis (WFMEA) to analyze the risks that occur and find members supply chain that has the greatest risk in the supply chain distribution channel Siam Banjar oranges in Barito Kuala Regency. From this research, it is found that the distribution channel of Siam orange Banjar in Barito Kuala Regency generally consists of farmers and traders, collectors, wholesalers and retailers and applied through five structures. A more accurate risk analysis result with the WFMEA method, value WRPN obtained for price risk (151.424), transportation risk (52.875), risk supply (52.380), quality risk (51.858), production risk (50.165) and risk environment (5.888). The results of the priority assessment of the Siam orange supply chain actors Banjar with the ANP method, namely farmers (0.371), traders (0.128), wholesalers (0.360) and retailers (0.142). Thus, members of the supply chain farmers who have the greatest risk. Keywords: Risk Analysis, Supply Chain, Siam Banjar Orange, Analytical Network Prosess (ANP)